GE_GERICHTE P/3096/2015 vom 26. August 2016 - GE Cour de justice (2016)
DISPOSITIONS PÉNALES DE LA LETR; FIXATION DE LA PEINE; RÉVOCATION DU SURSIS | LEtr.115.1.a; LEtr.115.1.b; CP.34; CP.42; CP.46; CP.47; CP.49; CPP.428; CPP.135